COMPUTER-MEDIATED COMMUNICATION AS A TOOL FOR IMPROVING THE ENGLISH LANGUAGE AMONG ADULT LEARNERS IN TVET PROGRAMME - Mohd Salleh, Berhannudin; Esa, Ahmad; Selamat, Asri; Othman, Hussain; Sulaiman, Abdulah; Suhaimy, Khairul Azman (Journal of Technical Education and Training, 2010)
This article highlighted the computer mediated communication skills students need to become lifelong learners in an information society. Among these skills are the abilities to: use technology tools to enhance learning; use telecommunications to collaborate with and interact with peers; use technology to locate and collect information from a variety of sources; and use technology for informed decision-making. The need to master the English language has always been a never ending quest especially among ESL adult learners in Malaysia. Mastery in the language will not only enhance academic achievements but promote one’s status in the community. Despite the many years of learning English command of the language among Malaysian ESL learners is still yet to be desired. This paper thus presents the findings of an innovative approach to learn the English language the technology way. Using an online platform that is freely available in the Internet participants comprising adult TVET teacher trainee of Universiti Tun Hussein Onn Malaysia took part in an online discussion using the English language via the Internet for a semester. Findings of the study revealed that the online platform has helped the students improve themselves in many aspects of the learning process. There was an increase in confidence and frequency of use of the target language, improved thinking ability and least but not last provided joy for learning the English language.